Estranha atração : a criação de categorias científicas para explicar os desejos pela deficiência - Gavério, Marco Antônio (Universidade Federal de São Carlos, 2017)
In the problematization of the insertion of the desire by disability, as sexual or identity pathologies, this project proposes an incursion into the terminology and biomedical configurations on the subject in order to understand which discourses are triggered when it is sought to discriminate as ‘sick’ those and those who seek to relate erotically to the disabled or who want to cause disabilities in their own bodies. For this, the intention is to investigate the clinical bibliography produced on devotees, pretenders and wannabes, aiming to systematize to the maximum historically the continuities and discontinuities in the creation of these 'pathological types'. Concomitantly, aiming to establish a critical dialogue with the biomedical knowledge on sexuality and disability, I propose a more theoretical theoretical incursion into one intersection between disability studies and queer theory, the so-called crip theory.
Keywords: Teoria queer; Corporalidades; Sociologia da deficiência; Desejo pela deficiência; Disability studies; Queer theory; Corporealities; Sociology of disability; Attraction to disability; CIENCIAS HUMANAS::SOCIOLOGIA